Gastroesophageal Reflux Disease: A Comprehensive Literature Review - Baiq Salwa Nadira Alifa; Velda Mufarrihati Jacindalya; Desak Putu Candraningtyas; M. Badzlul Rahmansyah; Alya Nabila Putri; Faiza Firdausy; I Nyoman Rhino Raditya; Safrizal Raditya Wardana; Syifa’ul Layaliy; Baiq Widya Kaweryan; Istiazah Ramadhani; Latifa Ainun Pratiwi; Muh. As’ad Hamzah (Jurnal Biologi Tropis, 2026)
Gastroesophageal Reflux Disease (GERD) is a chronic gastrointestinal disorder with increasing global prevalence that adversely affects quality of life and may lead to complications such as Barrett’s esophagus and esophageal adenocarcinoma. This narrative review aimed to synthesize current evidence on the pathophysiology, clinical manifestations, diagnosis, and management of GERD. A literature search was conducted using Google Scholar, PubMed, NCBI, and ScienceDirect for peer-reviewed articles and clinical guidelines published between 2021 and 2026. Twenty-two relevant articles in English and Indonesian were included. GERD results from an imbalance between aggressive factors, including transient lower esophageal sphincter relaxation, hiatal hernia, increased intra-abdominal pressure, and impaired esophageal motility, and the esophageal mucosal defense system. Non-Erosive Reflux Disease (NERD) is the most common phenotype, accounting for approximately 60–70% of cases. Diagnosis is based on symptom assessment supported by validated tools such as the GERD-Q questionnaire, ambulatory pH monitoring, and endoscopy when indicated. Proton pump inhibitors remain the first-line pharmacological therapy, complemented by lifestyle modification, while surgery is reserved for refractory or complicated cases. A patient-centered, evidence-based approach integrating early diagnosis, appropriate treatment, and patient education is essential to improve outcomes and prevent disease progression.